Modeling and analysis of task complexity in single-operator multi-robot teams - Özgelen, Arif Tuna; Sklar, Elizabeth I. (HRI '14 : proceedings of the 2014 ACM/IEEE International Conference on Human-Robot Interaction : March 3-6, 2014, Bielefeld, Germany, 2014)
A model is presented for analyzing the complexity of task assignment in a human/multi-robot team from the perspective of the human team member, or "operator". The focus is on complex domains where tasks have inter-dependencies and/or require tightly coupled coordination among robots. Preliminary validation of model metrics has been carried out through an experiment involving human subjects. Results suggest significant effect of key aspects of the model on human subjects' cognitive workload.